3D visual technology applied for the reconstruction of a Paleolithic workshop. (December 2019) - Zangrossi, Filippo; Delpiano, Davide; Cocilova, Arianna; Ferrari, Federico; Balzani, Marcello; Peresani, Marco
Highlights: 3D technology supports the reconstruction of Palaeolithic structures. Exploring spatial arrangements by 3D technology sheds light on the nature of a Palaeolithic workshop. Examination of stratigraphic patterns contributes to reconstruct the formation of lithic workshops. Virtual reconstruction enables us to restore information lost during excavation. Abstract: Archaeological investigations at the Paleolithic Piovesello open-air site in Italy have brought to light a small lithic workshop composed of 123 artefacts (Structure I). In order to remedy to the destructive nature of the excavation, we developed a conservative protocol based on a three-dimensional reconstruction of the heap, enabling us to restore information lost during the removals of the flakes. A 3D model of the structure and its close context was produced for each artefact through laser scanning, and then it was spatially positioned after the creation of a relative coordinate system using Structure from Motion with Agisoft Photoscan and by rectifying 24 photographs documenting different SI removal stages, performed by the software QGIS. Images provide X, Y coordinates of the findings located at the base of SI; for the Z coordinate is used the quote recorded during excavation. To reconstruct the formation process of the structure, we investigated its stratigraphy and performed the analysis according to different technological and morphometrical parameters, as core reduction stages, dimensional classes, presence of direct connections like refittings. Once Structure I has been interpreted like a primary workshop formed during knapping activities, it was possible to cross different data and to recognize six depositional stages, in which the alternation of large-size core shaping products, management flakes and fine full- production artefacts is visible.